Anti or Decolonialism in Latin America? A Current Debate - Ávila-Rojas, Odín (Sociedad y Economía, 2021)
The purpose of this paper is to analyze the current discussion on decolonization in political and ideological terms in Latin America. The methodology used is based on a documentary analysis review. Among the main conclusions of this article, we find that the difference between anticolonialism and decolonialism lies in their theoretical and historical starting point, as well as in the type of subjects that postulate them. Anticolonialism proposes the autonomy and ideological liberation of indigenous and Afro-descendant peoples, while decolonialism proposes to conceive the subjective capacity of these peoples from a universalist formulation of their ethnic and cultural particularity.